Acute blockade of NR2C/D subunit‐containing N‐methyl‐D‐aspartate receptors modifies sleep and neural oscillations in mice. (13th December 2020) - Pálfi, Emese; Lévay, György; Czurkó, András; Lendvai, Balázs; Kiss, Tamás
Abstract: N ‐methyl‐d ‐aspartate receptors (NMDARs) play an important role in excitatory neurotransmission and have been associated with psychiatric conditions including schizophrenia and major depressive disorder. NMDARs are composed of two NR1 and two NR2 subunits. The type of NR2 subunit determines electrophysiological and pharmacological properties of the receptor. As the precise role of NR2C/D subunit‐containing NMDARs is poorly understood in vivo, we have performed behavioural, quantitative electroencephalographic (qEEG) and polysomnographic analysis following acute pharmacological blockade of these receptor subtypes in adult male CD1 mice. We found that NR2C/D blockade impaired motor coordination and decreased the amount of gross movement. Moreover, EEG power in multiple frequency bands including theta and sigma were found to decrease significantly together with a decrease of theta oscillation frequency. Changes of these qEEG measures were accompanied by a decrease in time spent in slow‐wave and rapid eye movement sleep, but an increase of time spent in quiet wakefulness. Furthermore, there was a significant decrease of sleep spindle oscillation density. These findings highlight the importance of NR2C/D‐containing NMDARs and take a step towards establishing a link between electrophysiological correlates of psychiatric disorders and underlying synaptic dysfunctions.